Pakute – an Assyrian ‘Ghost Castle’ on the Rania Plain - Eidem, Jesper (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2018)
New evidence from the Rania Plain (Northeastern Iraq) reveals that foundations tablets of Tiglath-pileser I, pertaining to the restoration of ancient Pakute, come from the site of Basmusian. The implications of this discovery are briefly explored in the context of other Middle Assyrian sites in the region.